Crystallisation of ferrous sulphate heptahydrate: experiments and modelling - Shaikh, Latif; Pandit, Aniruddha; Ranade, Vivek (Canadian Journal of Chemical Engineering, 2013)
Crystallisation is an industrially important unit operation for purifying and separating chemical mixtures. A generic crystallisation modelling framework has been implemented in the general process modelling system (gPROMS) software (of PSE, UK). This framework can be used to model the batch cooling crystallisation of ferrous sulphate heptahydrate (FSH). The parameter estimation and sensitivity of the predicted results with various numerical parameters was studied for batch crystalliser. An Excel front-end to the gPROMS model was developed to facilitate the interactive use of the model. (c) 2011 Canadian Society for Chemical Engineering
Keywords: batch crystallisation; ferrous sulphate heptahydrate; gPROMS; MSExcel-linking; parameter estimation